2019
DOI: 10.1002/adfm.201907656
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Redox Kinetics, Electronic Structures and Electrode/Electrolyte Interfaces for Fast and High Energy‐Density Potassium‐Organic Battery

Abstract: Potassium-organic batteries have a great potential for applications in large-scale electricity grids and electric vehicles because of their low cost and sustainability. However, their inferior cycle stability and more importantly low energy density under fast discharge/charge process of organic cathodes limit their applications. This work introduces a simple polymerization processing which enables comprehensive tuning of redox kinetics, electronic structures, and electrode/electrolyte interfaces of the polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 58 publications
1
67
0
Order By: Relevance
“…PIs contain redox-active aromatic imide monomers that can be used as cathode materials in KIBs. Tong et al [68] have shown that the electrochemical properties of PTCDA-based PIs can (Fig. 7b).…”
Section: Aromatic Imidesmentioning
confidence: 95%
“…PIs contain redox-active aromatic imide monomers that can be used as cathode materials in KIBs. Tong et al [68] have shown that the electrochemical properties of PTCDA-based PIs can (Fig. 7b).…”
Section: Aromatic Imidesmentioning
confidence: 95%
“…In comparison, for the concentrated electrolyte systems, the decrease of the LUMO energy levels of anions caused by its interaction with K + ions leads to a preferen tial anion reduction reaction. [32,104,107,171] For example, a thinner anionderived SEI layer was formed in the electrolyte of 2.5 m KPF 6 /DEGDME compared with that in 1 m KPF 6 /DEGDME, thus enhanced performance was achieved on KVOPO 4 and K 1.69 Mn[Fe(CN) 6 ] 0.85 •4H 2 O cathodes. [171] Also the KTFSIbased concentrated electrolytes, such as 5 m KTFSI/DEGDME, 5 m KTFSI/DME and 4 m KTFSI/EC:DEC, allow more TFSIions to reach the interface and can introduce a more compact and thinner SEI layer with a larger amount of inorganic spe cies.…”
Section: Concentration Dependency Of Sei Layermentioning
confidence: 99%
“…Although redox kinetics have a significant impact on rate performance, the related research is rare: to date, only one research report by Tong [31] et al is available. They could easily adjust the electrochemical performance and redox kinetics of PTCDA‐based polymers (PTCDA‐ k C ( k =0, 2, 3, 4), 25 , Figure 11) by changing the length of the alkyl chain.…”
Section: Polymersmentioning
confidence: 99%